Atomically Precise Water‐Soluble Graphene Quantum Dot for Cancer Sonodynamic Therapy. Issue 19 (17th January 2022) - Ju, Yang‐Yang; Shi, Xiao‐Xiao; Xu, Shu‐Yu; Ma, Xiao‐Hui; Wei, Rong‐Jing; Hou, Hao; Chu, Cheng‐Chao; Sun, Di; Liu, Gang; Tan, Yuan‐Zhi
Abstract: Although water‐soluble graphene quantum dots (GQDs) have shown various promising bio‐applications due to their intriguing optical and chemical properties, the large heterogeneity in compositions, sizes, and shapes of these GQDs hampers the better understanding of their structure‐properties correlation and further uses in terms of large‐scale manufacturing practices and safety concerns. It is shown here that a water‐soluble atomically‐precise GQD (WAGQD‐C96 ) is synthesized and exhibits a deep‐red emission and excellent sonodynamic sensitization. By decorating sterically hindered water‐soluble functional groups, WAGQD‐C96 can be monodispersed in water without further aggregation. The deep‐red emission of WAGQD‐C96 facilitates the tracking of its bio‐process, showing a good cell‐uptake and long‐time retention in tumor tissue. Compared to traditional molecular sonosensitizers, WAGQD‐C96 generates superior reactive oxygen species and demonstrates excellent tumor inhibition potency as an anti‐cancer sonosensitizer in in vivo studies. A good biosafety of WAGQD‐C96 is validated in both in vitro and in vivo assays. Abstract : A water‐soluble atomically‐precise graphene quantum dot (WAGQD) with deep‐red emission is synthesized and shows a superior sensitizing potency for cancer sonodynamic therapy. The general synthetic strategy will enable the synthesis of WAGQDs with different sizes, edges, and tailored properties for further bio‐applications.